Integrating the Project-Based Learning (PjBL) Model into Basic Science Instruction to Promote Eco-Literacy Attitudes in the Context of Islamic Science Education - Zohrawaty Hiola; Frida Maryati Yusuf; Abubakar Sidik Katili (Jurnal Penelitian Pendidikan IPA, 2026)
This study addresses a persistent gap in science education—the limited integration of spiritual values and environmental stewardship into classroom practice. The research investigates how Project-Based Learning (PjBL) can promote students’ eco-literacy attitudes within the framework of Islamic science education. Employing a library research design and content analysis, the study examines books, journals, and related scholarly works focusing on PjBL, eco-literacy, and Islamic educational values. The findings reveal that PjBL enhances conceptual understanding and fosters active, contextual, and ethically informed scientific inquiry guided by Islamic principles. It also promotes eco-literacy through three interrelated dimensions: cognitive (knowledge of ecological systems), affective (concern for nature), and conative (environmental responsibility and action). The study concludes that integrating PjBL with Islamic values provides a coherent pedagogical framework that strengthens students’ scientific, moral, and ecological competencies. This approach is recommended for Islamic higher education institutions seeking to develop educators who are scientifically proficient, environmentally aware, and spiritually grounded